STUDI KOMPARASI KONSEP TUHAN MENURUT BARUCH DE SPINOZA DAN KARL THEODOR JASPERS - Siswadi, Gede Agus (Fakultas Dharma Duta dan Brahma Widya, 2023)
Recognizing God in empirical knowledge is indeed very difficult and even impossible to understand the reality of God. Philosophers and theologians both have different understandings of God, so that from the time of Ancient Greece to modern human civilization, there is no agreement about God. Various views of God emerged along with the development of human thought. Various characters appear with different concepts. This research focuses on examining the thoughts of Baruch de Spinoza and Karl Theodor Jaspers. This research uses a philosophical hermeneutic method. The results of this research are as follows: according to Spinoza, God is a single substance and has many attributes, everything in this universe comes from God. Spinoza also thought that the universe was identical with God. Meanwhile, according to Jaspers God is a mystery and transcendence. God can only be trusted, but cannot be recognized as an empirical object. God also cannot be reached by logical thinking. God can only be understood as a metaphysical reality.